Signifikansi Hadis Riwayat Dalam Menangani Konten Negatif Di Media Sosial - Azmi Fauziah Suanda; Tajul Arifin (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
In the digital era filled with social media, the spread of negative content has become a phenomenon threatening the integrity and security of the digital environment. This paper outlines the impact and challenges of disseminating negative content and reviews efforts to address it from the perspectives of Islamic law and positive law, emphasizing the importance of the hadith of Prophet Muhammad (peace be upon him) stating, "Verily, among the signs of a person's goodness in Islam is that he leaves what does not concern him" (Narrated by Tirmidhi). From the perspective of Islamic law, Muslims are invited to live their digital lives with integrity, morality, and awareness of their moral responsibilities. Principles such as selectivity in content consumption, guarding the purity of the heart, and spreading goodness serve as the foundation for Muslims in using social media. Meanwhile, positive law provides a framework for regulating the use of social media, including addressing the spread of negative content. Through strict regulations and effective law enforcement, it is hoped that a safe and positive online environment can be created for all users. Thus, addressing the phenomenon of negative content dissemination on social media requires a holistic approach that combines religious values, moral principles, and legal regulations, with the hadith of Prophet Muhammad serving as the main pillar in leading a dignified and beneficial digital life for all individuals.